The prevalence of malnutrition in children with cleft lip and cleft palate: a case-control study - V., Shashidhar; Dhanwadkar, Sharanabasappa S.; N. B., Ashwini Kumari; Kurle, Ravikumar; Navale, Rakesh A. (International Journal of Contemporary Pediatrics, 2019)
Background: Children with cleft lip and cleft palate come across lot of impediment, hurdles in society. There are several social factors which hinders the proper nourishment of CL only, CP or CLP children, so majority of them tend to suffer malnutrition due to lack of standard care especially from their parents and society. Due to even low socio-economic status, impact on growth of these children is vexatious. However potential risk of malnutrition is particularly more during early childhood. Moreover, till date there are not much significant data on malnutrition in CL only, CP or CLP children. The aim of the study was to assess the prevalence of malnutrition in non syndromic CL only, CP or CLP in south India. Methods: Anthropometric parameters weight for age z score (WAZ), height for age z score (HAZ), of children with CLP were compared with age matched controls. Results: Prevalence of PEM and stunting for cleft group were 40% and 21.3% respectively compared to 33.33% and 17.33% for the control. Differences in the underweight, and stunting between the two groups were not statistically significant (χ2=2.83, p value=0.58, and χ2=1.48, p value=0.69 respectively). Conclusions: There is no statistically significant difference in the occurrence of malnutrition in children with non- syndromic cleft lip and Palate compared with control.